Chapter 3 Social Spaces (2020)
"This first volume of The Class Structure of Capitalist Societies offers a bold and wide-ranging assessment of the shape and effects of class systems across a diverse range of capitalist nations. Plumbing a trove of data and deploying cutting-edge techniques, it carefully maps the distribution of the key sources of power and documents the major convergences and divergences between market societies old and new. Establishing that the multidimensional vision of class proposed decades ago by Pierre Bourdieu appears to hold good throughout Europe, parts of the wider Western world and Eastern Asia, the book goes on to examine a number of significant themes: the relationship between class and occupation; the intersection of class with gender, religion, geography and age; the correspondences between social position and political attitudes; self-positioning in the class structure; and the extent of belief in meritocracy. For all the striking cross-national commonalities, however, the book unearths consistent variations seemingly linked to distinct politico-economic regimes. This title will appeal to scholars and advanced undergraduate and postgraduate students interested in sociology, politics and demography and is essential reading for all those interested in social class across the globe."